A review on tourist experience quality – Systematic review and bibliometric analysis - Bandara, W. M. A. H.; Ranasinghe, J. P. R. C.; Dassanayake, D. M. C. (Goodwood Publishing, 2025)
Purpose: This study summarizes, synthesizes, and presents the existing empirical knowledge on tourist experience quality from to 2002-2023. Research Methodology: Systematic Literature Review methodology recommended reporting items, and PRISMA guidelines were used to achieve the above-mentioned objective. Based on predetermined seven inclusion criteria 50 papers were obtained from Lens.Org, Google Scholar, Emerald Insight, Tailor, and Francis. Every paper obtained was prepared in Lens.ORG format. Further, Biblioshiny and VOSviewer-based mathematical tools such as Keyword Co-Occurrence Analysis were employed to analyze the content and structure of papers. Results: The researcher found four themes, including (01). Tourist Contentment (02). Perceived Performance (03). Future Travel Behaviors (04). Tourist Wellbeing. Thus, Destination Image, Satisfaction, and Tourist Loyalty were the keywords of the first theme. Perceived Values and Perceived Risks were the keywords of the second theme. The only keyword of the third theme was behavioral intentions. The fourth theme was authenticity and QoL. Moreover, the findings emphasized that Tourist Experience quality had been investigated by many researchers in relation to satisfaction, behavioral intentions, and destination image perceived value. However, few studies have been undertaken on perceived risk, authenticity, and quality of life related to tourist experience quality. Conclusion: The study analyzed tourist experience quality research from 2002-2023 to, identifying four themes by meeting systematic literature review requirements. Limitations: This study obtained papers only from the aforementioned databases. Thus, future researchers could obtain papers from other databases. Contribution: This study assists government, non-government organizations, and academics in developing improved techniques, concepts, and service developments related to tourist experience quality.